2006
DOI: 10.1037/0894-4105.20.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Is implicit sequence learning impaired in Parkinson's disease? A meta-analysis.

Abstract: The aim of the present study was to examine impairment of implicit learning in Parkinson's disease (PD) by means of a meta-analysis of studies that used the serial reaction time (SRT) task. The authors performed a systematic review and meta-analysis of published journal articles (1987-2005) that used the SRT task with patients with PD. The principal outcome measures used to compare studies were (a) the difference in reaction time between the last block of ordered sequence trials and the randomized block for PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 29 publications
(28 reference statements)
8
118
1
1
Order By: Relevance
“…Siegert et al 2006), whereas other investigators have suggested that DA may not be involved in the processing of sequential learning (for discussions on these opposed findings, see Werheid et al 2003;Badgaiyan et al 2007;Vandenbossche et al 2009). Nevertheless, models which propose the involvement of DAergic basal ganglia processes in sequential behavior are widely accepted (Graybiel 1998;Da Cunha et al 2009;Schwarting 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Siegert et al 2006), whereas other investigators have suggested that DA may not be involved in the processing of sequential learning (for discussions on these opposed findings, see Werheid et al 2003;Badgaiyan et al 2007;Vandenbossche et al 2009). Nevertheless, models which propose the involvement of DAergic basal ganglia processes in sequential behavior are widely accepted (Graybiel 1998;Da Cunha et al 2009;Schwarting 2009).…”
Section: Introductionmentioning
confidence: 98%
“…On the basis of clinical SRTT studies in which Parkinson's disease patients showed deficits in sequential learning (for review see Siegert et al, 2006) and imaging studies revealing striatal recruitment during sequential learning (e.g., Werheid et al, 2003;Badgaiyan et al, 2007), various models were proposed that suggest a crucial role for dopaminergic processes in the striatum in sequential learning (Graybiel, 1998;Doyon and Ungerleider, 2002;Packard and Knowlton, 2002;Da Cunha et al, 2009;Schwarting, 2009). In a recent series of experiments using our rat version of the SRTT (Domenger and Schwarting 2005, 2007, we were able to lend further empirical support to the models' notion of the dependency of sequential learning on striatal dopamine availability Schwarting, 2008, Eckart et al, 2010a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Disease of these brain regions has been associated with impaired procedural memory. Individuals with Parkinson's disease are impaired on procedural memory tasks, such as probabilistic classification learning and motor sequence learning (Knowlton et al, 1996;Siegert, Taylor, Weatherall, & Abernethy, 2006;Wilkinson, Khan, & Jahanshahi, 2009). Conversely, a study with the famous amnesic individual, H. M., showed that while he had profound declarative memory impairment due to medial temporal lobe damage, he was able to learn how to use a stylus to perform a mirror tracing task.…”
Section: Procedural Memory and Toolsmentioning
confidence: 99%